Mengeksplorasi Pandangan Positivisme dalam Pendidikan - Sarumpaet, Ria Natalia Damayanti (Yayasan Sembilan Pemuda Indonesia, 2024)
The philosophy of positivism is an approach that emphasizes empirical observation as a valid basis for knowledge. This philosophical science emphasizes the scientific method and deductive reasoning and considers knowledge that can be empirical as valuable knowledge. There are several things found in positivism in education, namely in the development of educational curricula, learning methods, learning strategies and evaluation of learning learners currently used. This article examines the path of positivism philosophy from a historical perspective with a focus on its influence on human thinking in education. This article aims to provide deeper knowledge regarding the philosophical foundations and their influence on modern thinking in the world of education through critical observations of positivist concepts such as verification, experience, and scientific methodology.